1999
DOI: 10.1126/science.284.5418.1362
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Nuclear Receptor for Bile Acids

Abstract: Bile acids are essential for the solubilization and transport of dietary lipids and are the major products of cholesterol catabolism. Results presented here show that bile acids are physiological ligands for the farnesoid X receptor (FXR), an orphan nuclear receptor. When bound to bile acids, FXR repressed transcription of the gene encoding cholesterol 7alpha-hydroxylase, which is the rate-limiting enzyme in bile acid synthesis, and activated the gene encoding intestinal bile acid-binding protein, which is a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
1,820
5
23

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 2,411 publications
(1,919 citation statements)
references
References 18 publications
41
1,820
5
23
Order By: Relevance
“…Hirano,et al page 13 receptor, farnesoid X receptor (Wang et al, 1999;Makishima et al, 1999;Parks et al, 1999); farnesoid X receptor binds to DNA as a heterodimer with retinoid X receptor, recognizing an inverted hexanucleotide repeat separated by a single base (an IR-1 motif) (Forman et al, 1995). Although no IR-1 element has been identified in the RANTES promoter, further study should examine whether interaction between farnesoid X receptor and PPAR is related to inhibitory effects of fibrates on chenodeoxycholic acid-induced RANTES gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Hirano,et al page 13 receptor, farnesoid X receptor (Wang et al, 1999;Makishima et al, 1999;Parks et al, 1999); farnesoid X receptor binds to DNA as a heterodimer with retinoid X receptor, recognizing an inverted hexanucleotide repeat separated by a single base (an IR-1 motif) (Forman et al, 1995). Although no IR-1 element has been identified in the RANTES promoter, further study should examine whether interaction between farnesoid X receptor and PPAR is related to inhibitory effects of fibrates on chenodeoxycholic acid-induced RANTES gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their emulsifying properties are essential for digestion of dietary fat and lipophilic vitamins. In the last decade, bile acids were additionally discovered to be natural ligands of the farnesoid X receptor (FXR) [1][2][3], a nuclear transcription factor through which they regulate their own biosynthesis via a negative feedback. Moreover, it is now well established that FXR activation by bile acids results in the regulation of various genes involved not solely in bile acid homeostasis but also in cholesterol, triglyceride and glucose metabolism [4][5][6][7][8][9].…”
Section: Abbreviationsmentioning
confidence: 99%
“…In 1999, some groups found that bile acids were the natural ligands of FXR, which is since known as the BAR [12,13]. FXR is expressed abundantly in liver, intestines, kidneys, etc.…”
Section: Introductionmentioning
confidence: 99%